Fenomena Perceraian Dini Pada Masyarakat Modern: Perspektif Nilai Qiwamah Dan Sakinah Dalam Rumah Tangga Muslim - Putri Janati, Ade; Erina Pane; M. Dani Fariz Amrullah. D (Kartika: Jurnal Studi Keislaman, 2026)
The growing phenomenon of early divorce in modern society, particularly among Muslim families, has sparked deep academic concern given the high rate of divorce within less than five years, which contradicts ideal Islamic values. This study aims to analyze the root causes of early divorce from the perspective of the values of qiwamah (husband’s leadership) and sakinah (domestic harmony), as well as to formulate solutions. The research method is qualitative with a qualitative-normative approach; the data used consists of secondary data, sourced from primary, secondary, and tertiary legal sources. The results indicate that a weakening understanding of qiwamah as the husband’s responsibility to provide emotional and material support, coupled with a lack of sakinah due to the influence of modernity such as individualism and social media constitutes the primary trigger for early divorce. Therefore, this study recommends strengthening premarital education based on Islamic values in mosques and marriage institutions, as well as state policies for family counseling that integrate qiwamah and sakinah, in order to build the resilience of Muslim families in the modern era